Strategi Efektif dalam Penggunaan Model Biosistem : Menyusun Asumsi Dasar untuk Keberlanjutan Lingkungan - Ahmad, N; Eko Sutrisno; Sholikhah, F; M. Adik Rudiyanto (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This article discusses effective strategies for using biosystem models to achieve environmental sustainability. With increasing global challenges such as climate change, biodiversity decline, and growing food demand, the application of the biosystem model is becoming increasingly relevant. The model integrates ecological principles and appropriate technology, which enables efficient and sustainable management of natural resources. Through an analysis of the basic assumptions underlying the use of the biosystem model, this article identifies key elements that can improve agricultural productivity while maintaining ecosystem balance. The implementation of techniques such as crop rotation, agroecology, and the utilization of modern technologies such as automation and biotechnology are expected to strengthen food security and reduce negative impacts on the environment. The results from this study show that collaboration between the government, academia, and the private sector is essential to foster innovation and practice